Narrativas fílmicas e educação das artes visuais percursos, afetos e bricolagens na formação inicial de professores - Rosa, Aline Nunes da (2010)
The present paper is a research based on the experience with an experienced investigative group made up of five teachers in initial training of the Bachelor's Degree in Visual Arts in Federal University of Santa Maria / RS / Brazil. Understanding the film narratives as devices capable of producing emotions, awake and arouse desires, provoke assemblages and participate in the construction of our subjectivity, we released a series of propositions, organized in the form of meetings, in order to discuss and understand the presence/permanence of these filmic narratives in the production of life narratives of teachers who cooperated with the research. The research was based on the concept of bricolage to develop methodological issues concerning this study and used it to think of themselves as bricoleurs subjects, able to compose from fragments, clippings and overlapping of images and information everyday. The authors participating in this fabric are theoretical: MARTINS (2007, 2008, 2009), Hernández (2005, 2007, 2009), Oliveira (2009); LARROSA (2002, 2004, 2006); ROLNIK (2006), among others who have their speeches reviewed in this research. Thus, seeking how to perform such procedures, we could notice that the film narratives participate in the life of these employees eventually trigger choices, preferences, perceptions and world views, reverberating in ways that each of these employees are teachers as teachers of visual arts.